Correlational study: verbal creativity and personality according to the Big Five Model in Brazilian students - Nakano, Tatiana de Cássia (2016)
In Brazil, few studies are found investigating the relationship between creativity and personality constructs, especially considering the Big Five Model. This study investigated a sample of 83 Brazilian high school students, between ages 14 and 18 years (M = 16.01, SD = 0.95) that answered two questionnaires, the Torrance Thinking Creatively with Words (Brazilian version) and the Bateria Fatorial de Personalidade (Factorial Battery of Personality). The results indicated significant correlations only between the socialization factor and twoverbal creative indexes (ICVI = .26; ICVII = .26). In the present study the investigated constructs are weakly related. The influence of the instrument and the theoretical modeladopted in the findings is discussed.